Tumor estromal gastrointestinal - Mendívil, Rolando (2010)
Gastrointestinal stromal tumors are the most frequent mesenchimal neoplasms of gastrointestinal tract. They arise more frequently in the stomach and have a broad clinical spectrum. We report the case of a fifty-seven year-old female with history of two day gastrointestinal bleeding. The patient underwent surgical resection and the diagnosis was done using CD117 and CD34 markers. Though surgical resection is the only definitive treatment new therapeutic models are in development that use molecular targeted drug therapy. Various clinical essays are currently in course and some of them show promising results.